Feature Extraction and Matching from images / lntan Syaherra Ramli - Ramli, lntan Syaherra (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Feature Extraction and Matching are crucial in computer vision and graphics. This is a fundamental task for many applications such as 30 point cloud reconstruction and pattern recognition. In this task, feature extraction is used to detect the unique feature point from the images. The unique features depend on the type of images captured from different types of acquisition apparatus such as jpeg, png and dicom. Then, the feature matching algorithm is used to find the corresponding feature point between two or more images. Figure 1 shows the various feature extraction and matching methods. Meanwhile, Figure 2 shows the illustration of feature extraction and matching from 20 images using the jpeg file types. In this example, the features from images were extracted using Good Feature to Track. Next, the feature points from two images are matched using Optical Flow Lucas Kanade. The corresponding feature points are used to find the 30 point cloud for computer graphic application. The 30 point cloud used to represent the real object.